An annual flowering population of Neelakurinji Strobilanthes kunthianus (Nees) T. Anders. – a plietesial species from the Nilgiri sholas, India - Jose, Franklin Charles (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract